Survey of understanding and awareness of fertility preservation in pediatric patients: Is conversation about fertility preservation unpleasant for pediatric patients? - Takae, Seido; Iwahata, Yuriko; Sugishita, Yodo; Iwahata, Hideyuki; Kanamori, Ryo; Shiraishi, Eriko; Ito, Kaoru; Suzuki, Yuki; Yamaya, Yoshiko; Tanaka, Kunihide; Oyama, Kei; Keino, Dai; et al. (Frontiers in Endocrinology, 2023)
Objective: To verify understanding and awareness of fertility preservation (FP) in pediatric patients undergoing FP treatments. Methods: A questionnaire survey was conducted before and after explanation of fertility issues and FP treatments for patients 6–17 years old who visited or were hospitalized for the purpose of ovarian tissue cryopreservation (OTC) or oocyte cryopreservation (OC), or sperm cryopreservation between October 2018 and April 2022. This study was approved by the institutional review board at St. Marianna University School of Medicine (No. 4123, UMIN000046125). Result: Participants in the study comprised 36 children (34 girls, 2 boys). Overall mean age was 13.3 ± 3.0 years. The underlying diseases were diverse, with leukemia in 14 patients (38.9%), brain tumor in 4 patients (11.1%). The questionnaire survey before the explanation showed that 19 patients (52.8%) wanted to have children in the future, but 15 (41.7%) were unsure of future wishes to raise children. And most children expressed some degree of understanding of the treatment being planned for the underlying disease (34, 94.4%). Similarly, most children understood that the treatment would affect their fertility (33, 91.7%). When asked if they would like to hear a story about how to become a mother or father after FP which including information of FP, half answered “Don’t mind” (18, 50.0%). After being provided with information about FP treatment, all participants answered that they understood the adverse effects on fertility of treatments for the underlying disease. Regarding FP treatment, 32 children (88.9%) expressed understanding for FP and 26 (72.2%) wished to receive FP. “Fear” and “Pain” and “Costs” were frequently cited as concerns about FP. Following explanations, 33 children (91.7%) answered “Happy I heard the story” and no children answered, “Wish I hadn't heard the story”. Finally, 28 of the 34 girls (82.4%) underwent OTC and one girl underwent OC. Discussion: The fact that all patients responded positively to the explanations of FP treatment is very informative. This is considered largely attributable to the patients themselves being involved in the decision-making process for FP. Conclusions: Explanations of FP for children appear valid if age-appropriate explanations are provided.